GASTRO-PROTECTIVE EFFECT OF CROSSOPTERYX FEBRIFUGA IN WISTAR RATS. - Salawu, Adeola Oluwakanyinsola; Tijani, Yahaya A.; Hafsatu, Babayi; Nwaeze, Chinwe Angela; Ezeonu, Chidimma MaryJane; Igwe, Sunday; Ndukuba, Mary Adanna (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Preparations of Crossopteryx febrifuga (Afzel.) Benth. (Rubiaceae) are widely used in Northern Nigeria in the therapeutic management of trypanosomiasis, malaria and painful inflammatory disorders. Previous studies have shown that the methanolic stem bark extract of Crossopteryx febrifuga possesses significant analgesic and anti-inflammatory properties possibly mediated via Non-selective inhibition of cyclo-oxygenase pathways. In the present study, the methanolic stem bark extract of Crossopteryx febrifuga was evaluated against ethanol- and piroxicam-induced ulceration in rats. Histopathological studies of the rat stomach tissues were also carried out in order to determine its safety profile on the gastrointestinal tract (git). The extract (25, 50 and100 mg extract/kg body weight) significantly (P<0.05) and dose-dependently reduced ulcer index induced by ethanol (24 - 92%) and piroxicam (81.81- 98.60%). Histopathology of the rat stomach tissues from control and extract-treated groups at 25 mg/kg body weight extract showed mild inflammation characterized by infiltration of inflammatory cells, while the extract treated groups at 50 and 100mg/kg body weight and 200 mg misoprostol/kg body weight group showed no obvious lesions. These results showed that the extract had no deleterious effects and was cytoprotective on the gastrointestinal tract (git). It can thus be developed as a safe alternative to conventional non-steroidal anti-inflammatory drugs (NSAIDs) for the management of painful inflammatory disorders.